Basic business concepts principle and challenge of forage seed producer - Tarekengn, Abenet (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Forage Seeds Production as a Business Learning workshop. Presentation in Addis, Ababa, Ethiopia May 24th-25th, 2022.